THE EFFECT OF INVENTORY TURN OVER, FIXED ASSET TURN OVER, RETURN ON FIXED ASSET, AND RETURN ON EQUITY ON FINANCIAL PERFORMANCE REGIONAL PUBLIC SERVICES AGENCIES - Ependi, Ependi; Dalesna, Dalesna (Journal of Industrial Engineering & Management Research, 2021)
: This study uses quantitative research methods and the data used are primary data, namely annual financial reports. The population in this study was the Financial Services Agency for the Regional Public Health Center, Kramat Jati District in 2018 and 2019. Sampling in this study used purposive sampling technique. Based on the sampling technique above, the sample in this study was the Kramat Jati District Health Center. The data analysis technique was started with descriptive statistical test, then continued with panel data regression analysis, panel model selection method, classical assumption test consisting of regression normality test, heteroscedasticity, multicolonierity test and autocorrelation test. Hypothesis testing using multiple linear regression, t test, F test and coefficient of determination.The results of this study indicate that partially inventory turnover has no significant effect on financial performance, fixed asset turnover does not have a significant effect on financial performance, return on fixed assets does not have a significant effect on financial performance, and returns on equity have no significant effect on financial performance financial performance. Simultaneously, Inventory Turn Over, Fixed Asset Turn Over, Return on Fixed Asset, and Return on Equity together have no influence on the Financial Performance of Regional Public Service Bodies. The adjusted R-Square value is 0, meaning that the coefficient of determination is 0. The rest is 100% influenced by other variables outside the regression model in this study such as managerial ownership.